Effects of bensulfuron-methyl residue on photosynthesis and chlorophyll fluorescence in leaves of cucumber seedlings - Sun, Lanlan (PLoS One, 2019)
A potted soil experiment was conducted to investigate the effects of bensulfuron-methyl (BSM) residue on the growth and photosynthesis of seedlings of a local cucumber variety (Xia Feng No.1). When the residue of bensulfuron-methyl in soil exceeded 50μg kg(-1), it significantly inhibited the growth of cucumber, chlorophyll content and photosynthetic capacity of cucumber. BSM treatment caused significant decreases in the biomass, chlorophyll content, net photosynthesis rate, stomatal conductance, and transpiration rate, photosystem II (PSII) maximum quantum yield, actual quantum yield, photochemical quenching coefficient, and electron transport rate in cucumber seedlings, but increased the minimal fluorescence yield and dark respiration rate. Moreover, comparisons of the patterns of absorbed light energy partitioning revealed that the fractions of excess and thermally dissipated energy increased with rising concentrations of the BSM residue, but the fraction of PSII photochemistry declined. The BSM residues caused reversible destruction in the PSII reaction centers and decreased the proportion of available excitation energy used in PSII photochemistry. The results suggested that rice or wheat fields sprayed with BSM will not be suitable for planting cucumbers in succession or rotation.